How to staycation like a snail - Hrab, Naseem (Owlkids Books, 2024)
"Snail is an epic explorer. Well ... kind of. He especially loves the quiet things about adventures, like reading maps, collecting souvenirs, and finding wonder around every corner. And Snail knows that not all adventures need to be far-away -- they can also be near-away! -- which is why he and Stump choose a vacation destination a mere stone's throw from home. Snail and Stump smell the smells, listen for the sounds, and take in the sights of their home. And then something astonishing happens when a group of parachute seeds blows into their neighbourhood. Snail and Stump offer to show the seeds the sights, and as the seeds ooh and ahh over their favourite haunts, the two friends find an even deeper appreciation for their home and are able to see it in a whole new light."--